Analytical Evaluation of Nonlinear Amplify-and-Forward Relay Systems for OFDM Signals - Guerreiro, João (2017)
Amplify-and-forward relay techniques combined with OFDM (Orthogonal Frequency Division Multiplexing) modulations are being considered for broadband wireless systems since they allow simple relay systems suitable for severely time-dispersive channels. However, since they rely in OFDM-based signals, these techniques are prone to nonlinear distortion effects. In this paper we consider OFDM-based amplify-andforward relay systems with strong nonlinear distortion effects at both the transmitter and the relay node and we present a simple, but accurate, analytical method for characterizing the distortion levels at the subcarrier level.